(untitled) (Journal of Tourism & Adventure, 2024)
Protected areas are the cornerstone of global biodiversity conservation initiatives, and people’s support is pivotal for their success. However, in many protected areas, particularly those with restricted human interaction, the park-people relations deviated towards negativity, and the major cause is the inability of the park to connect conservation with the people’s livelihood. Better-planned tourism can serve as a vehicle to link conservation with livelihood, particularly in protected areas like Chitwan National Park (CNP), where the flow of tourists is already higher. However, there is a need to understand consumer satisfaction and link those to ensure a sustainable tourism business in the park. The aspect has been explored to a limited extent in the park; thus, we have attempted to partially address that void. To address the issue, we have collected the perceptions of the people through a face-to-face interview using a structured questionnaire with 142 tourists encountered in and around the Sauraha area of CNP. The data was collected in January 2020, was managed using Microsoft Excel, and was analyzed using R software. Natural attractions around the national park were found to be the important drivers that drive tourists to CNP, and they admired the accommodation (79% positive response), food (65% positive response), hospitality (75% positive response), and behavior of the local people (74% positive response). The majority of the tourists have a positive response towards other tourism amenities. Tourists were highly satisfied with the elephant safari and Jeep safari activities. However, many have suggested improving the transportation facility and solid waste management in the park. The findings of the studies can be used by the relevant stakeholders to improve the services and amenities offered to tourists, which will ensure the sustainability of tourism businesses in and around the park.